Novel Nano-composites SDC–LiNaSO4 as Functional Layer for ITSOFC - Lv, Weiming; Tong, Ze; Yin, Yi-Mei; Yin, Jiewei; Ma, Zi-Feng (Nano-Micro Letters, 2015)
As an ionic conductive functional layer of intermediate temperature solid oxide fuel cells (ITSOFC), samarium-doped ceria (SDC)–LiNaSO4 nano-composites were synthesized by a sol–gel method and their properties were investigated. It was found that the content of LiNaSO4 strongly affected the crystal phase, defect concentration, and conductivity of the composites. When the content of LiNaSO4 was 20 wt%, the highest conductivity of the composite was found to be, respectively, 0.22, 0.26, and 0.35 S cm−1 at temperatures of 550, 600, and 700 °C, which are much higher than those of SDC. The peak power density of the single cell using this composite as an interlayer was improved to, respectively, 0.23, 0.39, and 0.88 W cm−2 at 500, 600, and 700 °C comparing with that of the SDC-based cell. Further, the SDC–LiNaSO4(20 wt%)-based cell also displayed better thermal stability according to the performance measurements at 560 °C for 50 h. These results reveal that SDC–LiNaSO4 composite may be a potential good candidate as interlayer for ITSOFC due to its high ionic conductivity and thermal stability.